Clustering of Exogenous Organic Material Properties to Improve Their Efficient Recycling in European Agriculture - Michaud, Aurélia Marcelline; Caradec, Lucille; Tampio, Elina; Laakso, Johanna; Jimenez, Julie; Houot, Sabine (Wiley-Blackwell, 2026)
Exogenous organic materials (EOMs) are increasingly used as substitutes for mineral fertilizers and as tools to restore soil health within a circular bioeconomy context. However, the great diversity of EOMs in terms of origin, composition, chemical properties, and contaminant concentrations challenges their safe and efficient use in agriculture. The aim of the study was to establish a framework for the clustering of EOMs properties from several EU countries, enabling their categorisation according to their origin, characteristics, and chemical properties and trace elements (TE) profile. For that purpose, a dataset with chemical characteristics and TE concentrations from 118 EOMs was constructed from a database previously published. The EOMs included a wide range of organic residues and waste streams from agricultural, industrial, and urban origins representative of the diversity of European EOMs. Clustering analyses were carried out to distribute EOMs among clusters (i) of chemical properties based on their characteristics (dry mass, C-to-N ratio, pH, and concentrations of organic C, N, N-NH4, P, K, Ca, and Mg), and (ii) of TE profile based on their concentrations of As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn. Five practical scenarios of EOMs applications mixing amending and fertilizing EOMs were considered to estimate input fluxes of C, N, P, K, and TEs over a period of 10 years in contrasted areas (agricultural settings and peri-urban areas). The present study clustered the EOMs according to their soil improver characteristics that is, from NK fertilizing to liming and organic amending properties. The clustering analysis on TEs classified EOMs according to their TE profiles, with (i) smaller concentration of TEs (i.e., three quarters of EOMs), and (ii) larger concentration of all TEs and especially for Cu and Zn. The various practical scenarios simulating the repeated applications of local EOMs from contrasted areas showed that input fluxes were in line with commercial organic fertilizer inputs and below the goal of 170 kg N per hectare per year, while TE input fluxes respected the French regulation thresholds, even in the scenarios including EOMs containing also greater TE levels.
Keywords: chemical properties; exogenous matter; nutrients; organic fertilizers; soil improvers; trace elements